A Social-Economic Study of Small and Marginal Farmer in Resent Scenario: An Analytic Study of Social and Economic Conditions of Small and Marginal Farmers in Bhuj Taluka, Gujarat (Journal of Advances and Scholarly Researches in Allied Education, 2018)
India is an agricultural country. The majority of the farmer are small and marginal farmers having a land below 5 acres. These farmers are living on or below poverty line. The income of farmers determined by the size of holding. Higher the size of holding is higher the income potential. Higher is the income potential higher is socio-economic status. Present Study is related with the group of small and marginal farmers in Bhuj taluka of kutch district in the state of Gujarat. This study is devoted to an analytic study of social aspects of Socio-Economic conditions of the small and marginal farmers.